An Australian trial of the effectiveness of a discount reward to increase plasma donor retention and frequency of donation. (1st March 2021) - Chell, Kathleen; White, Claire; Karki, Surendra; Davison, Tanya E.
Abstract : Background and Objectives: Encouraging existing plasma donors to donate more frequently is a key objective for blood collection organizations committed to improving plasma self‐sufficiency through voluntary non‐remunerated donations. The aim of this paper is to present results from a pilot trial testing whether an in‐centre discount voucher reward could increase retention and donation frequency among new and repeat plasma donors. Materials and Methods: A sample of n  = 1242 new and repeat plasma donors who presented to donate at the Civic Plasma Donor Centre in Canberra, Australia, over a 14‐week period participated in the trial. Of this group, n  = 253 were offered a discount voucher for a local cafe (intervention group) and n  = 989 received the business as usual approach in the donor centre (control group). The subsequent donation behaviour of participants was monitored over three months. Results: Overall, 69·6% accepted the discount voucher, with 18·2% of those redeeming it. Those who accepted the voucher were younger and less experienced plasma donors. The intervention did not significantly increase the likelihood of return to donate compared to the control group; however, it did reduce the time to return to donate plasma. The overall rate of donation within 3 months was also significantly higher for donors who were offered the incentive than for the control group. Declining the offer did not negatively impact donors' return behaviour. Conclusion: This paper provides new insights around strategies to increase plasma donation frequency, as well as donor response to introducing a discount voucher reward within a voluntary non‐remunerated donation system.